ACDI/VOCA-AICCRA Internship Program - ACDI/VOCA (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
To accelerate inclusive and gainful employment for young women and men in Zambia, ACDI/VOCA, under its USAIID EDGE project, developed an internship program. ACDI/VOCA partnered with the Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project to deliver a joint program centered around building capacities of interns in business management skills, key value chain practices, climate information services (CIS) and climate-smart agricultural (CSA) practices.